Analysis the water in aggregate glue droplets of spider orb web by TOF‐SIMS. (1st December 2020) - Zhao, Yue; Morita, Masato; Sakamoto, Tetsuo
Abstract : Orb‐weaver spiders of the family Araneidae produce a viscous glue from aggregate glands. Spiders effectively capture prey by coating the viscous glue onto the spiral lines. The viscous glue has an unusual property. The main components are glycoproteins, salts (low molecular mass compounds [LMMCs] and inorganic salt), and water. The interaction of water and glycoproteins relies on the presence of salts. Here, we used a freeze method to analyze the behavior of water of the viscous glue using time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS). We found that the matrix effect of glycoprotein may cause ion suppression of water in aggregate glue droplets. Moreover, the changes in element distribution before and after the viscous glue adheres to the object suggest that after losing salts, water not only ceases to interact with glycoproteins but also oozes with the salts.